Association study of TREM2 polymorphism rs75932628 with leucoaraiosis or Parkinson's disease in the Han Chinese population. Issue 1 (12th January 2016) - Li, Zhiming; Zhong, Li; Gu, Long; Huang, Wenqing; Shi, Xinzhen; Zhang, Xilin; An, Xingkai; Lin, Qing; Tzeng, Chi-Meng
Abstract : Objectives: The previously reported functional mutation rs75932628-T (p.R47H) in the triggering receptor expressed on myeloid cells 2 (TREM2) is a genetic risk factor for Alzheimer's disease, Parkinson's disease (PD) and frontotemporal dementia, in European populations. This study aims to assess the genetic association of the variant rs75932628-T with PD and leucoaraiosis (LA) in a Han Chinese population. Setting: This population-based study was conducted in China by Xiamen University and its affiliated hospital. Participants: 308 patients with LA, 342 patients with PD and 198 healthy blood donors were recruited from the First Affiliated Hospital of Xiamen University. Outcome measures: Genotyping was performed by molecular beacon real-time PCR and Sanger sequencing. Results: None of our participants carried the rs75932628-T mutation. Conclusions: Our results corroborate and extend previous findings, concluding that the variant rs75932628-T (p.R47H) in TREM2 is not a risk factor for LA or PD in the Han Chinese population.